Headache attributed to hypothyroidism - Carvalho, Marise de Farias Lima; Vilar, Lucio; Carvalho, Anderson Henrique Ferreira; Medeiros, Josian; Mendonça, Caio Max Félix; Gomes, Barbara Guiomar Sales; Lyra, Eliabe Alves; Moraes, Paulo Ranieri Araújo; Albuquerque, Anúzia; Valença, Marcelo Moraes (Headache Medicine, 2010)
Headache and hypothyroidism are clinical conditions that cause major impact in the quality of life. It is well known that hypothyroidism and headache are both more frequent in women. Hypothyroidism is a common disease clinically recognized as a complex syndrome with signs and symptoms affecting most if not all parts of the body. Headache is one of the most common symptoms of hypothyroidism, estimated to occur in about one third of the patients. In the ICHD 2nd edition (2004), the headache attributed to hypothyroidism (HAH, 10.4) was included in the group of secondary headaches and it was described as bilateral, non pulsatile and continuous and must be present in patients with clear diagnosis of hypothyroidism. Moreover, the treatment of hypothyroidism is supposed to relieve or lead do complete resolution of this type of headache. We reviewed the literature regarding the prevalence of headache in hypothyroid patients, its characteristics considering the criteria of ICHD II, and possible differences between the group with headache and the group without headache.